The Macmillan world atlas (Macmillan, 1997)
That makes one atlas better than another? Accuracy, up-to-date information, ease of use, attractive maps, completeness, utility, authority. All these features come together in the The Macmillan World Atlas and are set off by a presentation of unparalleled beauty